A nimble organization and a flexible degree program: A term‐based competency‐based education case study. Issue 2 (28th March 2019) - Herron, Joshua; Garland, Eleisha
Abstract: Anderson University began re‐designing one of its online degrees using competency‐based education principles in 2015, using almost 2 years to develop the curriculum and implementation plans. The model is designed with maximum flexibility, letting students choose their path to competency at each course rather than developing both subscription and term models. In the term‐based model that the university uses, students are able to add courses within a term if they finish sooner mid‐session since courses allow for varying paces and paths all aligned to a set of program competencies developed through national standards for the profession and input from the program's advisory board. Investment by the university leadership, a dedicated implementation team, and a nimble organization allowed a successful program launch in fall 2018, overcoming many common barriers cited to achieve the benefits of increased program quality, alignment to competencies, higher retention and completion, and positive enrollment trends.